Jizhong Finite temperature effects in the Fermi liquid theory of the diffusion of 4He in 3He - Hjort, H. H.; Culman, T. G.; Edwards, D. O.; He, Jizhong (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The diffusion coefficient D and the thermal diffusion ratio kT, for dilute 4He in liquid 3He, are calculated from Fermi liquid theory. The collision integral assumes a scattering amplitude a34 expanded in scalar combinations of the quasiparticle momenta. As T -> 0, D varies as 1/T and kT/c, where c is the concentration, approaches a constant. As shown previously, the limits for DT and kT/c are determined by thermodynamic properties, the 4He effective mass and partial volume, and properties of pure 3He. We have decreased kT/c by a few percent, by including the effect of simbol T on the 3He distribution function. The temperature dependence of DT and kT/c is linear and related to the coefficients in the expansion of a34. Two coefficients can be found from thermodynamics. A conjecture about the remainder suggests that DT may have a maximum between 0 and 0.5K.